Selecting strategies and developing the business continuity plan - Henderson, Douglas M. (Henry Stewart Talks, 2011)
Business Continuity Plan development, Information gathering and Analyzing, Business impact analysis, The risk event chain, Risk assessment, Strategy development and selection, Risk treatment, IT alternate sites, Office alternate sites, Temporary structures as alternate sites, Manufacturing alternatives, Bunker strategy, Pre-positioning